2011
DOI: 10.1111/j.1752-9824.2011.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Whose job is it? Gender differences in perceived role in heart failure self-care

Abstract: dickson vv, worrall‐carter l, kuhn l & riegel b (2011) Journal of Nursing and Healthcare of Chronic Illness3, 99–108
Whose job is it? Gender differences in perceived role in heart failure self‐care Aim.  To describe gender differences in perceived role in heart failure (HF) self‐care and to explore how an individual’s perception of their role influences self‐care behaviours. Specifically, two hypotheses were tested: (1) there are gender‐specific differences in perceived self‐care roles in HF and (2) there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…We found that when faced with competing personal goals, for example childcare versus managing symptoms, participants chose the action most compatible with their personal goals. This finding is consistent with our prior work in which we found that when other roles and responsibilities compete with self-care, decisions are affected (Dickson, Kuhn, , Worrall-Carter, & Riegel, 2011;Dickson, McCauley, & Riegel, 2008).…”
Section: ML Sanz De Acedosupporting
confidence: 93%
“…We found that when faced with competing personal goals, for example childcare versus managing symptoms, participants chose the action most compatible with their personal goals. This finding is consistent with our prior work in which we found that when other roles and responsibilities compete with self-care, decisions are affected (Dickson, Kuhn, , Worrall-Carter, & Riegel, 2011;Dickson, McCauley, & Riegel, 2008).…”
Section: ML Sanz De Acedosupporting
confidence: 93%
“…Previous studies have found that male gender is a significant predictor for self-care maintenance 31 and management. 43 Some factors may impact men and women differently. 43 Some factors may impact men and women differently.…”
Section: Discussionmentioning
confidence: 99%
“…50 In this study, higher perceived social support was a significant predictor of better self-care maintenance and higher confidence in self-care abilities. Dickson and colleagues 43 found that regardless of the support, patients who took a passive role and relied on others for direction and help in managing symptoms had poorer self-care. 15,31,32 It may be that social support is more critical to success with self-care maintenance and improving confidence in patients with MCI.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, even among those who weigh themselves daily, lack of skill in evaluating the data obtained 32 and using it to manage symptoms (eg, diuretic titration) results in poor self-care. 33 Finally, the action or behavior chosen must be compatible with one's values. Values can be defined broadly as preferences concerning appropriate courses of action or outcomes and reflect one's sense of right and wrong.…”
Section: Factors Influencing Decisions About Self-carementioning
confidence: 99%